Recent development and future application of biodegradable ureteral stents - Hu, Ke; Hou, Zhipeng; Huang, Yuanbin; Li, Xueying; Li, Xiancheng; Yang, Liqun (Frontiers in Bioengineering and Biotechnology, 2024)
Ureteral stenting is a common clinical procedure for the treatment of upper urinary tract disorders, including conditions such as urinary tract infections, tumors, stones, and inflammation.Maintaining normal renal function by preventing and treating ureteral obstruction is the primary goal of this procedure. However, the use of ureteral stents is associated with adverse effects, including surface crusting, bacterial adhesion, and lower urinary tract symptoms (LUTS) after implantation. Recognizing the need to reduce the complications associated with permanent ureteral stent placement, there is a growing interest among both physicians and patients in the use of biodegradable ureteral stents (BUS). The evolution of stent materials and the exploration of different stent coatings have given these devices different roles tailored to different clinical needs, including anticolithic, antibacterial, antitumor, antinociceptive, and others. This review examines recent advances in BUS within the last 5 years, providing an in-depth analysis of their characteristics and performance. In addition, we present prospective insights into the future applications of BUS in clinical settings.